Comparison of Music Genre Classification Results Using Multilayer Perceptron With Chroma Feature and Mel Frequency Cepstral Coefficients Extraction Features - Rina Refianti; Faradilla Mahardi (Department of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2023)
The development of digital music, especially in genre classification has helped in the ease of studying and searching for a song. There are many ways that can be used to classify the songs/music into genres. Deep Learning is one of the Machine Learning implementation methods that can be used to classify the genre of music. The author managed to create a deep learning-based program using the MLP model with two extraction features, Chroma Feature and MFCC which can classify song/ music genres. Pre-processing of the song is done to take the features of the existing value then the value will be incorporated into the model to be trained and tested. The model was trained and tested with data of 3000 songs which were divided into 10 genres. The model was also tested using the Confusion Matrix with 600 songs of the total available data. The models with Chroma Features as extraction features have an accuracy rate of 53 %, while the MFCC extraction features have an accuracy rate of 80.2 %.